MENTAL HEALTH OF WOMEN IN KERALA: THE NEED FOR A GENDER PERSPECTIVE - MRIDUL EAPEN
Much has been written about the "high" status of women in Kerala and their central role, historically, in its development based on the remarkable achievements in the social sectors. This is reflected in the highest levels of literacy and health for Kerala women among the states of India. More recent works highlightthe state's weaker position if health indicators like "morbidity" (in lieu of "mortality") were considered. Besides there is growing uneasiness with equating status thus defined and empowerment. The emerging contradictions in social development between the very high physical health indicators and the alarming growth in female suicides, manifesting extreme mental distress gives some urgency to the study of women's mental health problems in Kerala.